2022
DOI: 10.21776/ub.jpa.2022.010.01.1
|View full text |Cite
|
Sign up to set email alerts
|

CRYSTALLINE AND DIGESTIVE CHARACTERISTICS OF HEAT MOISTURE TREATED AND ANNEALED LESSER YAM (Dioscorea esculenta) STARCH

Abstract: Hydrothermal modification is a physically safe modification applied in a food product to enhance its functional properties and to extend the starch application in the food industry. Heat Moisture Treatment (HMT) and Annealing (ANN) affect the starch’s functional properties in its crystalline and digestive characteristics. Native starch is modified by HMT with 25% moisture content and 4 hours heating time, by ANN with starch and water ratio of 1:3 (w/w), and 10 hours at 50°C. Modified lesser yam starch by HMT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our XRD analyses also showed that HMT decreased the crystallinity degree in cassava, consistent with a previous report [36], where the crystalline degree (decreased by HMT) was attributed to the lower amylopectin compounds and structural changes in crystalline type A-B. The A-type structure was indicated by the crystalline arrangement of amylopectin chains [28]. The A-type crystalline structure displayed firm diffraction peaks of 2Ɵ = 15° and 23°, while the crystalline structure of type B displayed medium diffraction peaks at 15° and 23° [35,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our XRD analyses also showed that HMT decreased the crystallinity degree in cassava, consistent with a previous report [36], where the crystalline degree (decreased by HMT) was attributed to the lower amylopectin compounds and structural changes in crystalline type A-B. The A-type structure was indicated by the crystalline arrangement of amylopectin chains [28]. The A-type crystalline structure displayed firm diffraction peaks of 2Ɵ = 15° and 23°, while the crystalline structure of type B displayed medium diffraction peaks at 15° and 23° [35,37].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, HMT also affected amylose and amylopectin content in cassava; amylose content increased at the expense of amylopectin after HMT. A previous study reported that high HMT temperatures broke amylopectin-branched chains at 1–6 glycoside bonds, leading to linear double helix short chains, or amylose [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being able to improve the characteristics of starch, both single and multiple modifications increase the resistant starch content of raw materials in several commodities such as arrowroot [16], sweet potato [17], mung beans [18], and lesser yam [13]. Resistant starch is the part of starch that cannot be digested in the small intestine and will be fermented in the large intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Physical starch modification methods that have been widely applied recently include heat moisture treatment (HMT) and annealing to modify native starch. The starch modification process with the hydrothermal principle increase heat stability and reduce retrogradation ability so that it is suitable for application to pasta and bakery products [13]. Heat moisture treatment (HMT) is a physical starch modification technique in which starch with low moisture (18%-30%) is heated for several hours at a relatively high heating temperature (range 90-120 °C) or above the transition temperature, below the gelatinization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the birefringence pattern indicate changes that occur in the starch granules are HMT modifications have different effects on starch and flour granules for each type of starch and treatment. Several factors affect the morphology of starch granules during HMT, including internal factors (amylose and amylopectin composition), as well as conditions before and during modification (temperature, humidity, time, and pressure) [87,88]. These factors trigger an increase in starch polymer chain interactions to associate or strengthen bonds between amylose-amylopectin chains, which are referred to as aggregation and agglomeration processes [26,56].…”
mentioning
confidence: 99%